PH-responsive selenium nanoparticles stabilized by folate-chitosan delivering doxorubicin for overcoming drug-resistant cancer cells. (1st February 2018) - Luesakul, Urarika; Puthong, Songchan; Neamati, Nouri; Muangsin, Nongnuj
Graphical abstract: Highlights: pH-responsive SeNPs for delivery of DOX to resistant cancer cells were prepared. It could enhance activity of DOX about 10 folds the IC50 value decreasing in resistant cells. DOX-loaded SeNPs@TMC-FA demonstrated a faster release rate under acidic condition. DOX-SeNPs@TMC-FA induced cell death through apoptosis pathway. pH-responsive SeNPs as targeted nanocarriers promoted efficacy of DOX and overcome resistance. Abstract: Herein, we first report pH-responsive SeNPs stabilized with modified folic acid-N-trimethyl chitosan (TMC-FA) as nanocarriers for delivery of doxorubicin (DOX) to overcome drug-resistant cancer cells, which could enhance the activity of DOX by approximately 10-fold for a reduced IC50 value compared to free DOX. When nanoparticles were taken up by cells, the DOX-loaded SeNPs@TMC-FA demonstrated a faster release rate under acidic conditions. The cumulative release amount of DOX at pH 5.3 was 54.1% within 2 h and 95.5% at 6 h, whereas the release rate at pH 7.4 was 12.3% in 2 h and 42.2% for 6 h; release was not completed at the end of the study, 72 h. Mechanistic studies suggested that DOX-SeNPs@TMC-FA induced cell death through the apoptosis pathway by involvement of caspase-3 and PARP proteins. The results demonstrated that pH-responsive SeNPs@TMC-FA, as targeted nanocarriers, promoted the efficacy of DOX and overcame drug resistance in NCI/ADR-RES cells.